ALGORITHMIC PROCESSES AND LOGICAL SYSTEMS MODELING IN ANYLOGIC ENVIRONMENT TO OPTIMIZE COMPLEX SYSTEMS - Dilfuza Nishonova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This paper explores the application of algorithmic processes and logical systems modeling in the AnyLogic environment to optimize complex systems, particularly in the context of education. The study investigates various algorithmic approaches, simulation techniques, and optimization strategies to enhance system performance and decision-making. By analyzing different methodologies, this research aims to highlight the significance of logical modeling and simulation in improving efficiency and accuracy. Furthermore, it discusses the importance of integrating computational algorithms to support intelligent decision-making and process automation.